2010
DOI: 10.1016/j.jjcc.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term β-blocker therapy improves diastolic function even without the therapeutic effect on systolic function in patients with reduced ejection fraction

Abstract: The beneficial effects of beta-blocker therapy on the clinical outcomes of heart failure with reduced ejection fraction (HFREF) are attributed to the improvement in ejection fraction (EF) and left ventricular (LV) reverse remodeling. Previous studies only reported the beta-blocker therapy-induced improvement of diastolic function accompanied by the increase in EF in HFREF patients. This retrospective study aimed to elucidate whether beta-blocker therapy improves diastolic function even without an increase in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In our study, mitral E/A ratio was similarly reduced with carvedilol or nebivolol therapy due to reduction of mitral E wave velocity. This finding is in accordance with the results from previous studies [10,[18][19][20]22]. In contrast, Patrianakos et al [9] have reported that mitral E/A ratio was significantly decreased with nebivolol treatment in nonischemic HF patients at 12-month follow-up, but not with carvedilol therapy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, mitral E/A ratio was similarly reduced with carvedilol or nebivolol therapy due to reduction of mitral E wave velocity. This finding is in accordance with the results from previous studies [10,[18][19][20]22]. In contrast, Patrianakos et al [9] have reported that mitral E/A ratio was significantly decreased with nebivolol treatment in nonischemic HF patients at 12-month follow-up, but not with carvedilol therapy.…”
Section: Discussionsupporting
confidence: 91%
“…In HF patients with low EF, carvedilol therapy reduced mitral E velocity, E/A ratio and IVRT while it prolonged DT [18,20,22], as in our study. In contrast, mitral inflow velocities and mitral E/A ratio remained unchanged with carvedilol therapy in HF patients in previous two studies [9,10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Beta blockers (BB) have been shown to decrease death and re-hospitalization of patients with HF and reduced EF, 6,8,9 and have been endorsed in both guidelines and performance measures. 2 Consequently, this class of medications is an appealing, but unproven, choice for treating HF patients with preserved EF.…”
Section: Introductionmentioning
confidence: 99%